Fostering Self-Regulated Learning (SRL): Higher education students’ insights on formative online reflective journals - Ivana Arlene Wellington; Paulus Kuswandono (UNIB Press, 2026)
Journaling serves as a documented account of the thoughts and emotions experienced in daily life. This term has also been analyzed in the educational context, especially in language learning. In addition, online reflective journals have been the subject of multiple studies, but these studies have all involved teachers rather than students. Thus, the effect of formative online reflective journals on SRL among college students is investigated in this research. The data was evaluated using central tendency measurement after fifty-two students were asked to provide quantitative data on their perspectives on using reflective journals. Subsequently, five students were interviewed using a semi-structured interview to gather additional qualitative data. Additionally, document analysis was used in this investigation. The results show that students' SRL abilities may be significantly improved by using online reflective journals, which contribute to students' motivation, self-awareness, and metacognition. During this research process, educator administration, an appropriate method and the empowering of student learning environment are elements that affects reflective journals being active properly. The results of this study are anticipated to offer important insights on the use and efficacy formative online reflective journals, as one intervention tool for SRL among higher education students in a well-established university setting. More precisely, the outcomes guide us on responding to this research question: What are the key components of formative online reflective journals that support the development of self-regulated learning (SRL) among higher education students?